Unstudied infants: outcomes of moderately premature infants in the neonatal intensive care unit. Issue 4 (12th April 2006) - Escobar, G J; McCormick, M C; Zupancic, J A F; Coleman-Phox, K; Armstrong, M A; Greene, J D; Eichenwald, E C; Richardson, D K
Abstract : Background: Newborns of 30–34 weeks gestation comprise 3.9% of all live births in the United States and 32% of all premature infants. They have been studied much less than very low birthweight infants. Objective: To measure in-hospital outcomes and readmission within three months of discharge of moderately premature infants. Design: Prospective cohort study including retrospective chart review and telephone interviews after discharge. Setting: Ten birth hospitals in California and Massachusetts. Patients: Surviving moderately premature infants born between October 2001 and February 2003. Main outcome measures: ( a ) Occurrence of assisted ventilation during the hospital stay after birth; ( b ) adverse in-hospital outcomes—for example, necrotising enterocolitis; ( c ) readmission within three months of discharge. Results: With the use of prospective cluster sampling, 850 eligible infants and their families were identified, randomly selected, and enrolled. A total of 677 families completed a telephone interview three months after hospital discharge. During the birth stay, these babies experienced substantial morbidity: 45.7% experienced assisted ventilation, and 3.2% still required supplemental oxygen at 36 weeks. Readmission within three months occurred in 11.2% of the cohort and was higher among male infants and those with chronic lung disease. Conclusions: Moderately premature infants experience significant morbidity, as evidenced by high rates of assisted ventilation, use of oxygen at 36 weeks, and readmission. Such morbidity deserves more research.